On Affine Immersions with Flat Connections - Shugailo, O.O. (Журнал математической физики, анализа, геометрии, 2012)
In this paper, the multidimensional affine immersions with °flat connections of maximal pointwise codimension are studied. The estimates on the dimensions of kernel and the image of the shape (Weingarten) operator and the a±ne fundamental form are obtained. Some properties of nullity distributions on the immersed submanifold are considered and the examples of a±ne immersions of high codimension with flat connection are given. Изучаются многомерные аффинные погружения с плоскими связностями максимальной точечной коразмерности. Получены оценки размерности ядра и образа оператора Вейнгартена и аффинной фундаментальной формы. Установлены некоторые свойства нуль-распределений. Приведены примеры аффинных погружений высокой коразмерности с плоскими связностями.